Hepatitis B virus reactivation during direct-acting antiviral agent-based therapy for chronic Hepatitis C - Güçlü, Ertuğrul; Alan, Sevgi; Karabay, Oğuz (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Güçlü E, Alan S, Karabay O. Hepatitis B virus reactivation during direct-acting antiviral agent-based therapy for chronic Hepatitis C. Turk J Gastroenterol 2020; 31(4): 344-5.